Social Construction Of The Elite In The Quran (analysis Of Term Al-mala’) - Muhammad Yusuf; Mardan; Nahdhiyah; Kamaluddin Nurdin Marjumi (Institut Agama Islam Negeri Madura, 2024)
Vol. 29 No.1, June 2021( pp. 98-127)